Developing women entrepreneurs through guided and funded business start-ups in Cape Town - Jali, Someleze (Cape Peninsula University of Technology, 2021)
Cape Town is known for its diverse environment, which attracts many tourists and investors worldwide. Although women make up the majority of the population in South Africa, they make up a small percentage of business owners. Increasing the number of female entrepreneurs is envisioned to eradicate poverty and unemployment, enhance women empowerment, ensure equity, and boost South Africa's economy. The study examined women entrepreneurs' development through guided and funded business start-ups in Cape Town. Semi-structured interviews with 17 participants were used to collect data using a qualitative technique based on purposive sampling. Of this sample, 14 participants were women entrepreneurs and 3 were experts on women entrepreneurship. All the women entrepreneurs with work experience of over 15 years in the respective industries their businesses operate in, were classified as experts. The experts were included because of their role and experience in guided the funding that was provided to them. An interpretive paradigm and an explorative design were employed. The data was analysed using the Atlas.ti software. The privacy of all participants was protected, and the necessary permission letters and consent forms were retrieved before sampling started. The goal of the study and how the data would be utilized were explained to the participants. Participants were told that they could leave the interview at any time if they did not like it. The participants perceived that many women business start-ups are not funded nor guided. The findings revealed that many women entrepreneurs do not support one another in business start-ups in Cape Town. Moreover, very little efforts are put into interventions by both government and the private sector to abate gender discrimination and eliminate exclusion of women entrepreneurs. Proposed interventions to improve women entrepreneurship start-up funding and guidance include encouraging platforms for informal businesses to become formal and to invade the informal financial networks. Women’s entrepreneurial start-ups should receive guided funding support through financial aid, mentorship and skills development for managing a business, which can create job opportunities. Information regarding start-ups registrations, growth and development programmes must be publicized. The information provided will benefit women entrepreneurs, entrepreneurs, scholars, and other relevant stakeholders in South Africa.
Thesis (MTech (Business Administration in Entrepreneurship))--Cape Peninsula University of Technology, 2021
Keywords: Entrepreneurship; Women Entrepreneurship; Guided Funding; Start-ups